Coordinated tuning of PSS and TCSC-POD controller using an Elite Genetic Algorithm - Gamino, Bruno R. [UNESP]; De Araujo, Percival B. [UNESP]; Fortes, Elenilson De V.; Martins, Luis F. B.; Miotto, Ednei L. (Institute of Electrical and Electronics Engineers (IEEE), 2017)
In this article, an Elite Genetic Algorithm is applied for tuning the parameters of supplementary damping controllers. The strategy of the applied method is to ensure the permanence of elite solutions in the process without the loss of diversity at an early stage. The Power System Stabilizers and the Thyristor Controlled Series Capacitor-Power Oscillation Damping are placed in a symmetrical test system to provide additional damping for low-frequency oscillatory modes. A modeling by current injection for device TCSC is presented, it is incorporated into the Current Sensitivity Model, which is used to represent the electric power system. The results show that the Elite Genetic Algorithm has an interesting performance for the proposed problem, since it can find high quality solutions in a short time, qualifying the method as an important tool in the analysis of small-signal stability.
Keywords: Elite Genetic Algorithm; Power Oscillation Damping; Power System Stabilizers; Small-Signal Stability; TCSC